The potential for independent behaviour of children aged 4-5 with play methods - Pangestu, Muhammad Adji (Universitas Islam Malang, 2025)
The aim of this research is to successfully find out the playing method, to create a sense of independence in children.Independence is one aspect of character formation that is very important in early childhood, especially in the age range of four to five years, but in Indonesia there are still many children who have not achieved independence. This can be caused by several things, such as parents who are too loving and pampering their children, following all the wishes and desires of children and helping if children cannot do something. This study uses a literature review research method with qualitative content analysis using literature from various journals, such as Google Scholar, Sinta, DOAJ, Garuda, and so on. The results of the study show that the play method has a significant role in developing children's independence, including role play, constructive play, outdoor activities, and traditional games. Each type of game makes a unique contribution to developing different aspects of independence, such as decision making, problem solving, and responsibility. However, the implementation of the play method in Indonesia still faces challenges, especially related to the availability of parents' time for their children. This study concludes that the integration of various play methods in early childhood learning, supported by the active role of teachers and parents, is very important to optimize the development of children's independence.